1978
DOI: 10.1002/chin.197816123
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: ETHER UPS ANTIKNOCK OF GASOLINE

Abstract: Methyl‐tert.‐butyl‐ether (III) erhöht das Antiklopfverhalten von Benzingemischen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…ETBE is a relatively recent compound and there is little information available in the literature on its emissions (Baur et al 1990;Naman and Allsup 1980;Pecci and Floris 1977;Weber de Menezes et al 2006b;Wells 2008). Since it has been suggested as a candidate for replacing MTBE, it is nonetheless interesting to compare the two additives (MTBE and ETBE), as in the study by Baur et al (1990), on the same SI internal combustion engine.…”
Section: Etbe Emissionsmentioning
confidence: 99%
“…ETBE is a relatively recent compound and there is little information available in the literature on its emissions (Baur et al 1990;Naman and Allsup 1980;Pecci and Floris 1977;Weber de Menezes et al 2006b;Wells 2008). Since it has been suggested as a candidate for replacing MTBE, it is nonetheless interesting to compare the two additives (MTBE and ETBE), as in the study by Baur et al (1990), on the same SI internal combustion engine.…”
Section: Etbe Emissionsmentioning
confidence: 99%
“…Purification of methyl‐ tert ‐butyl ether (MTBE) and especially separation of a methanol and MTBE mixture are among the most challenging processes in the chemical industry. MTBE is one of a group of chemicals commonly known as oxygenates because they raise the oxygen content of gasoline and help gasoline burn more completely, thereby reducing harmful tailpipe emissions from motor vehicles. It has been shown that the addition of 10%–15% MTBE to gasoline increases the motor octane number by 2–5 .…”
Section: Introductionmentioning
confidence: 99%
“…The conventional separation process used for development of environmental senses in recent the reaction mixture is water washing and disyears. [1][2] Specifically, ethanol may be obtained tillation. Because ethanol combined with ETBE from farming products by fermentation, so ETBE can form an azeotropic mixture, a very complex flow sheet with several distillation columns was designed.…”
Section: Introductionmentioning
confidence: 99%